Sobre a identidade pessoal estendida e o status de pessoas dos ciborgues naturais : uma análise a partir do caso extremo dos portadores de Alzheimer - Ramos, Ronaldo de Oliveira (2020)
Based on questions about herself, the character Motoko, in the film Ghost in the Shell, wonders about her continuity over time and her human condition and as a person. Similarly, it is possible to entertain some scenarios in which the addition of elements external to the body produces a similar tension with respect to human persons. One of these scenarios is that of natural cyborgs, as understood by Andy Clark. Based on the notion of natural cyborgs, through the coupling of elements external to the body, not as artificial implants, but within a systemic whole for the realization of cognitive processes and mental states, it is possible to question the maintenance of personal identity and status as a person, as these external elements are increasingly dependent. This is especially true with Alzheimer’s patients. In this work, some notions are minimally clarified, such as extended mind, natural cyborgs and personal identity, which support the further discussion on the possibility of maintaining the personal identity and the status as a person for Alzheimer’s patients, along the progressive process of cognitive deterioration, through the understanding that they are natural cyborgs.